FRI0420 No Male Predominance in Offspring of Women with Rheumatoid Arthritis or Systemic Lupus Erythematosus. (10th June 2014) - Dar, L.; Weitzman, D.; Chodick, G.; Shalev, V.; Amital, H.
Abstract : Background: Women are known to respond more potently to infections, vaccinations, and to trauma with consequent enhanced antibody production. Novack et al [1] reported a strong predominance of males (63/91) among offspring born to 42 mothers with SLE, a finding perhaps indicating that the female genotypic expression by itself elicits an immune response which lead to premature termination in-utero of the development of female fetuses. Objectives: To assess the proportion of male versus female offspring of women diagnosed with SLE or RA, disorders in which female predominance is well known, as well as among women diagnosed with psoriatic arthritis (PsA), a disease in which female dominance is less established. Methods: The study population included all females aged 16 to 46, who were members of the Maccabi Health Services (MHS) throughout the period of January 2000-October 2011 and had at least one indication of pregnancy during this period. Data was retrieved from the computerized database of MHS, a 2-million enrollee health maintenance organization (HMO) operating in Israel. These automated datasets, have previously been described in length [2]. The obstetric history of these women was retrieved, including date of birth and sex of all offspring, and all abortions (spontaneous or induced), intrauterine deaths, and still births, with their respective dates. The automated database was also used to collect data on patients diagnosed by a rheumatologist with RA, SLE, and PA using the International Classification of Diseases (ICD) Ninth Revision (ICD-9) codes. Numbers and proportions with confidence intervals are presented for male sex and for pregnancy losses. Standard morbidity ratios (and confidence intervals) were calculated to adjust pregnancy losses before and after disease diagnosis for age. The population free of the above mentioned disorders served as the standard population. Results: A total of 182, 073 women had at least one indication of pregnancy during the study period. Among them, 546, 270, and 170, were diagnosed with RA, SLE, and PsA, respectively (Table 1). The proportion of live-born males in 380, 472 offspring of women free of these diseases was 51.5% (95% confidence interval: 51.4-51.7%). The proportion (95% CIs) of male offspring born to mothers diagnosed with of RA, SLE, and PsA were 46.3% (42.3-50.3%), 51.8% (46.6-57.0%), and 50.6% (42.8-58.5%), respectively. The proportion of pregnancy losses among SLE patients, was significantly higher than the proportion in the disorder-free population, both before and after diagnosis. This was not true for RA or PA patients. Conclusions: Our findings support the primary contribution of the hormonal phenotype rather than the genetic phenotype on autoimmunity. Neither patients with SLE or RA differ from the general population by the sex of their offspring. References: Novack V, Erez O, Novack L et al. stribution of newborns to mothers with systemic lupus erythematosus. Epidemiology 2006;17:341-342. Chodick G, Amital H, Shalem Y, et al. Persistence with statins and onset of rheumatoid arthritis: a population-based cohort study. PLoS Med. 2010 Sep 7;7(9):e1000336. doi: 10.1371/journal.pmed.1000336. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2559